Dream girl ebook - Lippman, Laura (2021)
Booklist Editors' Choice! Called One of the Best Mystery Books by NPR, Washington Post, Crime Reads, Library Journal, South Florida Sun-Sentinel, and Dublin City Library! "With this tip of the hat to Stephen King's Misery, Dream Girl is funny and suspenseful, with a dread-worthy final twist." —People "My dream novel. I devoured this in three days. The sharpest, clearest-eyed take on our #MeToo reckoning yet. Plus: enthralling." —Megan Abbott, Edgar Award-winning author of Dare Me and The Fever Following up on her acclaimed and wildly successful New York Times bestseller Lady in the Lake, Laura Lippman returns with a dark, complex tale of psychological suspense with echoes of Misery involving a novelist, incapacitated by injury, who is plagued by mysterious phone calls. Aubrey, the title character of Gerry Andersen's most successful novel, Dream Girl, is so captivating that Gerry's readers insist she's real. Gerry knows she exists only in his imagination. So how can Aubrey be calling Gerry, bed-bound since a freak fall? A virtual prisoner in his penthouse, Gerry is dependent on two women he barely knows: his incurious young assistant, and a dull, slow-witted night nurse. Could the cryptic caller be one of his three ex-wives playing a vindictive trick after all these years? Or is she Margot, an ex-girlfriend who keeps trying to insinuate her way back into Gerry's life? And why does no one believe that the call even happened? Isolated from the world, drowsy from medication, Gerry slips between reality and dreamlike memories: his faithless father, his devoted mother; the women who loved him, the women he loved. Now here is Aubrey, threatening to visit him, suggesting that Gerry owes her something. Is the threat real or a sign of dementia? Which scenario would he prefer? Gerry has never been so alone, so confused – and so terrified. And then he wakes up to another nightmare—a woman's dead body next to his bed—and the terrifying uncertainty of whether he is responsible.